2015
DOI: 10.1177/2049463715584408
|View full text |Cite
|
Sign up to set email alerts
|

The development and delivery of a female chronic pelvic pain management programme: a specialised interdisciplinary approach

Abstract: Context/Background: Chronic pelvic pain (CPP) is a physically and psychologically debilitating condition. European Association of Urology (EAU) Guidelines (2013) and Royal College of Obstetricians and Gynaecologists (RCOG) guidelines (2012) place strong emphasis upon multi-speciality assessment and liaison, as well as interdisciplinary assessment and intervention in reference to the management of CPP. Objectives: The aim was to introduce and describe the development and delivery of an interdisciplinary pain m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 23 publications
1
38
0
3
Order By: Relevance
“…Our findings confirm previous evidence for high levels of psychological distress and functional impairment associated with this condition,21 and extend these findings by including measures that are highly relevant to treatment planning, such as thinking styles and pain self-efficacy. Our findings confirm the need to move away from organ-focused approaches to pain, and use integrated models of pain to understand this condition 10,11…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Our findings confirm previous evidence for high levels of psychological distress and functional impairment associated with this condition,21 and extend these findings by including measures that are highly relevant to treatment planning, such as thinking styles and pain self-efficacy. Our findings confirm the need to move away from organ-focused approaches to pain, and use integrated models of pain to understand this condition 10,11…”
Section: Discussionsupporting
confidence: 75%
“…The importance of taking a multi-disciplinary approach to CPP was also highlighted in other recent studies 11,21. These authors found that functional impairment and pain interference were more strongly related to psychiatric symptoms, such as anxiety and depression, than to pain severity.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Неадекватное управление болью является источником значительных экономических затрат для пациентов, их семей и общества [7]. Эмоциональные переживания, связанные с болью и инвалидностью, могут быть изнурительными и оказывать выраженное воздействие на качество жизни [10,11].…”
unclassified